2007
DOI: 10.1071/mf05260
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine levels as indicators of the post-release survivorship of juvenile pelagic sharks caught on experimental drift longlines in the Southern California Bight

Abstract: Between 1983 and 2004, nearly 12 000 shortf in mako (Isurus oxyrinchus), common thresher (Alopias vulpinus) and blue (Prionace glauca) sharks were tagged in the Southern California Bight; however, only 1.97% of these have been returned. One possible reason for this low return rate could be post-release mortality caused by capture stress from the experimental longline. Plasma catecholamine levels were analysed to evaluate stress levels in longline-captured, rod-and-reel-captured and unstressed docile sharks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
1
32
1
Order By: Relevance
“…While there is evidence that indicates the short-term survival rate of released sharks can be high (Gurshin and Szedlmayer 2004;Moyes et al 2006;Hight et al 2007), these studies do not address the issue of longer-term mortality that may result from ingested hooks and associated disease. Peritonitis, intra-lesional bacteria and cachexi have been observed in blue sharks, Prionace glauca, with retained hooks (Borucinska et al 2001(Borucinska et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence that indicates the short-term survival rate of released sharks can be high (Gurshin and Szedlmayer 2004;Moyes et al 2006;Hight et al 2007), these studies do not address the issue of longer-term mortality that may result from ingested hooks and associated disease. Peritonitis, intra-lesional bacteria and cachexi have been observed in blue sharks, Prionace glauca, with retained hooks (Borucinska et al 2001(Borucinska et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Although, measuring these two variables was out of the scope of the present study, intramuscular lactate and plasma catecholamine may be good predictors of shark mortality following capture (Hight et al, 2007;Frick et al, 2012). Additional information on how these variables can influence capture condition can be used to determine the biological systems that are most detrimentally effected by fisheries capture and can help to design effective management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the likelihood of mortality increases with increasing sea surface temperature, temporal restrictions on fishing during some months could be enacted to reduce bycatch mortality. Predictive models can also be used to identify physiological thresholds at which immediate and post-release mortality are likely to occur (Moyes et al, 2006;Hight et al, 2007;Frick et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported both whole-blood and plasma lactate concentrations .23.3 mmol L À1 (the upper limit for the Lactate Pro) in several species of sharks, including Isurus oxyrinchus and Alopias vulpinus (Hight et al 2007), Prionace glauca (Moyes et al 2006), Rhizoprionodon terraenovae (Hoffmayer and Parsons 2001), Carcharhinus obscurus (Cliff and Thurman 1984;Mandelman and Skomal 2009) and C. plumbeus (Brill et al 2008). In the present study, diluting the whole-blood by 50%, whether using acidified saline, tap water or distilled water, provided a simple and reliable method for measurement of potentially off-scale lactate concentrations.…”
Section: Lactate Concentrations Outside the Meter Rangementioning
confidence: 99%
“…The relatively unique characteristics of elasmobranch blood -nucleated red blood cells and high levels of nitrogen products (Lai et al 1997) -make it essential that such testing occurs. In addition, because sharks can have whole-blood and plasma lactate levels .40 mmol L À1 (Hoffmayer and Parsons 2001;Hight et al 2007;Brill et al 2008), which is greater than the range of human values, and, hence, the range of the portable analyser, a method for addressing values higher than the upper detection limit is needed.…”
Section: Introductionmentioning
confidence: 99%